Design of catalyst systems for the one-pot synthesis of menthols from citral - Trasarti, Andres Fernando (2007)
Stable, active, and highly selective bifunctional Ni/Al-MCM-41 catalysts were developed for the one-pot synthesis of menthols from citral. The liquid-phase hydrogenation of citral to citronellal was studied on silica-supported noble (Pt, Pd, Ir) and nonnoble (Ni, Co, Cu) metals. It was found that citronellal is selectively formed at the beginning of the reaction only on Pd and Ni catalysts. The consecutive ene-cyclization of citronellal to isopulegols was investigated on solid acids containing exclusively Lewis (ZnO/SiO2) or strong Brönsted (CsHPA) acid sites, and also on catalysts containing both Lewis and Brönsted acid sites of either strong (zeolites, SiO2-Al2O3) or moderate (Al-MCM-41) strength. The isopulegol formation rate was higher on samples exhibiting dual Lewis/Brönsted acidity, such as SiO2-Al2O3, Al-MCM-41, and zeolite HBEA. Based on these previous results, bifunctional catalysts containing Pd or Ni supported on SiO2-Al2O3, Al-MCM-41, or zeolite HBEA were prepared and tested for citral conversion to menthols. The catalyst stability and the effect of hydrogen pressure and metal loading on menthol productivity were also investigated. The best catalyst was Ni(8%)/Al-MCM-41, which yielded more than 90% menthols at 2026.0 kPa and showed no significant deactivation after two consecutive catalytic tests.